Fringe stakeholder engagement in protected area tourism planning: inviting immigrants to the sustainability conversation. Issue 12 (2nd December 2017) - Khazaei, Anahita; Elliot, Statia; Joppe, Marion
ABSTRACT : Effective and inclusive community participation is an essential and challenging component of sustainable tourism planning and development, especially as communities become increasingly diverse. The establishment of national parks and other protected areas closer to urban areas provides a unique opportunity for investigating community engagement in diverse contexts, as park agencies are mandated to connect with a broader range of community stakeholders. Historically, the engagement of immigrants and minorities with parks and protected areas has focused primarily on visitation, while their role as members of host communities has for the most part been overlooked. This qualitative study, conducted during the development of Canada's first National Urban Park, addresses this need by providing a deeper understanding of immigrants' engagement in planning. In-depth, semi-structured interviews are conducted with planners, politicians, community organizations, and first-generation immigrants who are now community leaders. The study draws upon, and expands on, earlier work by McCool and by Bramwell. It recommends five underlying principles for more inclusive public conversations: adopting an ongoing, long-term, and communicative approach; being open to new perspectives and willing to revisit assumptions; designing parallel strategies and customized tactics; collaborating with community leaders; and engaging in short-term and long-term learning.